Right to Independent Living: Housing Solutions for People with Intellectual Disabilities - Durán Alonso, Silvia (Street Art & Urban Creativity, 2025)
Article 19 of the International Convention on the Rights of Persons with Disabilities includes the “Right to live independently and to be included in the community”. Likewise, art. 49.2 of the Spanish Constitution establishes that “the public powers will promote policies that guarantee the full personal autonomy and social inclusion of people with disabilities.” Along these lines, our Disability Law develops what is known as the “Principle of independent living”. In guarantee of this right, the so-called “sheltered housing” are configured as a valuable housing resource for people with cognitive impairment. Although, we find its uneven development, as social services are the responsibility of the Autonomous Communities. Through this work, it is intended to analyze the situation of this resource, as a means of integration of people with intellectual disabilities, and if there is a need to implement public policies aimed at its development.